Associations among diet, the gastrointestinal microbiota, and negative emotional states in adults. (1st December 2020) - Taylor, Andrew M.; Thompson, Sharon V.; Edwards, Caitlyn G.; Musaad, Salma M.A.; Khan, Naiman A.; Holscher, Hannah D.
ABSTRACT: Objective: Habitual diet impacts mood and the human gastrointestinal (GI) microbiota. Yet, studies infrequently control for diet when evaluating associations between mood and GI microbiota. Accordingly, we aimed to investigate relationships among diet, GI microbiota, and mood in adults without mood disorders by conducting a cross-sectional examination of dietary intake, subjective emotional state, and fecal microbial taxa abundances. Methods: Adults ( N  = 133; 25–45 years of age) without physician-diagnosed mood disorders were studied. Fecal DNA was extracted, and the V4 region of the 16S rRNA gene was sequenced. Sequences were analyzed using QIIME2. Subjective mood state was assessed using the 42-item Depression, Anxiety, and Stress Scale (DASS-42). Habitual dietary intake was measured with the National Cancer Institute's Diet History Questionnaire II, and diet quality was evaluated with the 2010 Healthy Eating Index (HEI). Results: Relationships were observed between 28 bacterial taxa and DASS-42 scores. Sex-dependent associations were observed among 21 bacterial taxa and DASS-42 scores, including an inverse relationship between Anxiety scale scores and Bifidobacterium in females and an inverse relationship between Depression scale scores and Lactobacillus in males. HEI total fruit and dairy components were inversely associated with Depression and Stress scales, respectively. Conclusions: These results suggest GI microbes are related to mood in adults without diagnosed mood disorders and that these relationships differ by sex and are influenced by dietary fiber intake. Incorporating dietary intake data in gut-microbiota-brain studies may help clarify the roles of specific microbes and dietary components in mental health symptoms.